Application of network-based virtual instrument technology for remote inspection of vehicle - SHAO Yong-hua; BAO Yi-dan; WANG Li-da (浙江大学学报. 农业与生命科学版, 2004)
A development module of network-based virtual instrument technology intended to be used for inspecting the performance of vehicle was presented. G web server provided by NI company helped achieve the web issue of vehicle inspection front panel. Meanwhile DataSocket technique helped achieve data transfer through internet. LabVIEW and web technology were combined to realize the remote control of vehicle inspection to meet the needs of clients. The system has been proved to be quite effective in performance examination of vehicle, such as brake horsepower, speed, noise, lamplight, smoke intensity and the weight of every axle.